Pertumbuhan Penduduk dan Kaitannya dengan Pembangunan Ekonomi - Dwi Khairunnisa; Putri Winanda; Laili Rohimah Pangaribuan (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The study examines the relationship between population growth and economic development, focusing on how demographic dynamics influence various economic aspects of a country. Rapid population growth can increase the labor force and market demand, potentially driving economic growth. However, significant challenges arise when population growth is not matched by job creation, adequate education, and sufficient infrastructure development. This research also explores the environmental impacts of unplanned population growth and emphasizes the importance of inclusive economic development to enhance societal welfare. By utilizing relevant data and case studies, the study provides insights into the strategies necessary to achieve a balance between population growth and sustainable economic development.